Preparation of Liquid Crystal Doped with Nanomaterials and Studying of Electrical and Dielectric Properties - Al-Senany, Nourah; Al-Ghamdi, Ahmed. A.; Al-Hazmi, Faten; Alnowaiser, Fowzia; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2014)
The effects of multiwall carbon nanotube on dielectric ansitropy and molecular reorientation properties of 4-hepty1-4'-cyanobiphenyl liquid crystal have been investigated. The 4-hepty1-4'-cyanobiphenyl liquid crystal exhibits the negative resitance effect at higher voltages (3.5 V), whereas rnultiwall carbon nanotube doped 4-hepty1-4'-cyanobiphenyl liquid crysatl shifts it to the lower voltages (0.3 V). The 4-hepty1-4'-cyanobiphenyl and multiwall carbon nanotube doped 4-hepty1-4'cyanobiphenyl liquid crystals indicate a p-type dielectric anisotropy behaviour. The multiwall carbon nanotube dopant increases the dielectric anisotropy Delta epsilon of 4-hepty1-4'-cyanobiphenyl as the dopant-used facilitates the reorientation of the molecules in liquid crystal. It is has shown that the negative resitance effect and molecular reorientation properties of the 4-hepty1-4'-cyanobiphenyl are changed with multiwall carbon nanotube dopant.
Keywords: Nano-Structures; Anisotropy; Liquid Crystal